Performance of Soil Subgrade Improvement using Waste Material Coconut Shell Charcoal - Putri, Lusi Dwi; Rahmawati, Cut; Ahmad, Jawad (International Journal of Engineering, Science and Information Technology, 2025)
This study investigates using Coconut Shell Charcoal (ABK) as a stabilizing agent for clayey soils, aiming to enhance their suitability for road subgrade applications. The primary objective is to evaluate the effect of varying ABK concentrations (0%, 5%, 10%, and 15%) on the geotechnical properties of clay soil, particularly its compaction and load-bearing capacity. Laboratory tests, including compaction and California Bearing Ratio (CBR), were conducted to assess the influence of ABK on soil strength and stability. The results reveal that adding ABK significantly improves the soil's compaction characteristics and CBR values. The highest improvement was observed at 15% ABK, where the CBR value reached 22.22%, well above the minimum threshold required for road subgrade materials. There is a good influence of coconut shell charcoal on increasing the CBR value of clay soil subgrade at each additional material. The R value of 0.963 obtained shows a very high correlation. The addition of coconut shell charcoal to the subgrade soil has a positive effect on the California Bearing Ratio value which increases in each variation. The study demonstrates that ABK, a sustainable agricultural waste product, provides an affordable and effective solution for enhancing the strength and stability of clay soils, making it a promising alternative to traditional stabilizers such as lime and cement. The findings have significant implications for road construction in regions with expansive and weak soils, offering a cost-effective and environmentally friendly method for soil stabilization. This research contributes to the growing body of knowledge on the use of agricultural waste in infrastructure development, emphasizing the potential of ABK in providing sustainable solutions for soil improvement in civil engineering applications.